1999
DOI: 10.1046/j.1525-1500.1999.99018.x
|View full text |Cite
|
Sign up to set email alerts
|

Dose-Response Relationship between Amphibole Fiber Lung Burden and Mesothelioma

Abstract: In a mesothelioma case-control study, asbestos and other mineral fibers from lung burden were examined as causal factors. Diagnosis was confirmed by a panel of pathologists. For 66 cases and 66 controls from hospitals in five German towns, lung tissue fiber analysis by transmission electron microscopy was available. Control patients were treated by a surgical lung resection mostly because of lung cancer. For chrysotile and other mineral fibers a significantly increased odds ratio (OR) was not observed. A clear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 13 publications
0
29
0
Order By: Relevance
“…Although this study had limited numbers, the other studies 1,4,7) also indicated that males have higher asbestos concentrations than females because males have greater exposure to the outdoors air, or asbestos-related occupations, than females. This study, however, can not be used to validate this matter due to the lack of the investigation on the past residential histories of the subjects.…”
Section: Discussionmentioning
confidence: 65%
See 3 more Smart Citations
“…Although this study had limited numbers, the other studies 1,4,7) also indicated that males have higher asbestos concentrations than females because males have greater exposure to the outdoors air, or asbestos-related occupations, than females. This study, however, can not be used to validate this matter due to the lack of the investigation on the past residential histories of the subjects.…”
Section: Discussionmentioning
confidence: 65%
“…Although there were no relationships between age and the fiber concentrations in some case-control studies 4,7) , the results were reversed in a study of 81 autopsies in Canada 1) . Therefore, a further study with greater sample numbers will be needed.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…Rödelsperger and colleagues 35 similarly reported that the concentration of amphibole 36 1991 Case-control study of mesothelioma patients Strongest correlation with crocidolite fibers 10 lm in length fibers exceeding 5 lm in length was associated with an increased odds ratio of mesothelioma and a clear doseresponse relationship. In addition, Rogers et al 36 found that the strongest correlation of relative risk of mesothelioma was with the concentration of crocidolite fibers that were at least 10 lm in length.…”
Section: Human Studiesmentioning
confidence: 97%